Antifungal evaluation of edible coating agent against Fusarium Oxysporum on tomato - Safari, Zahir Shah; Ding, Phebe; Atif, Ashuqullah; Salari, Mohammad Wali; Yusoff, Siti Fairuz (IJSTR, 2021)
Fusarium fruit rot is caused by Fusarium oxysporum is one of the damaging postharvest losses in tomato production. Synthetic pesticides are widely and repetitively used to control this disease, unfortunately, it lead to detrimental effects on human health, environment and increase fungal resistance. This study aimed to identify Fusarium oxysporum by both morphological and molecular characterization that caused tomato fruit rot, as well as to study the effects of edible coating agents in vitro towards Fusarium oxysporum mycelium growth. In this study, pathogenicity test showed Fusarium oxysporum is most sever fungi with disease severity 72%, as well as among coating agents 5% CaCl2 was able to inhibited mycelium growth of Fusarium oxysporum up to 53.5% and 15 mM vanillin up to 76.68%. This study proved that 15 mM vanillin has a potent natural antifungal agent against Fusarium oxysporum mycelium growth.